Effect of some factors on the hydrolysis process of sweet potat starch by spezyme alpha to produce isomaltooligosaccharide (IMO) - Duong, Quan Hong; Hoàng, Tri Minh; Tuyên, An Duy; Vu, Trang Thu; Luong, Nga Hong (Vietnam Journal of Science and Technology, 2022)
Isomalto-oligosacarides (IMOs) a mixture of glucooligosaccharides linked by α- (1 → 6) and/or a low proportion of α- (1 → 3) (nigerooligosaccharide) or α- ( 1 → 2) glycosidic bonds (kojioligosaccharide) included glucose oligomers linked together by α-D- (1,6) glycoside bonds such as: isomaltose, panose, isomaltotetose, isomaltotetose. IMO is considered as prebiotics found in several traditional foods such as rice miso, soybean sauce and sake, etc… In this article, the effect of some factors on hydrolysis of sweet potato starch by Spezyme Alpha to form oligossacharide with DP 2-6 before being branched were studied.